2011
DOI: 10.2298/tsci11s1053w
|View full text |Cite
|
Sign up to set email alerts
|

A novel optimized energy-saving extraction process on coffee

Abstract: In this paper, Taguchi method is applied to optimize ultrasound thermal process for extracting caffeine and flavor from coffee. The use of ultrasound can abridge experiments in cost, energy loss and time; the different operating conditions for extraction experiments are executed and the results are also compared. The results show that the best design factors for caffeine are 95℃ of extraction temperature, 28 kHz of operating frequency and 30 s of extraction time. The proposed optimized extraction method is eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…2. It can be seen that the temperature exerts great influence on caffeine recovery, similar to the ultrasound assisted caffeine extraction from coffee powder during preparation of coffee beverage (Wang et al 2011). Temperature contributes to the extraction efficiency, because it strongly affects the properties of the solvent (decrease of both viscosity and surface tension, and induces an increase in the vapor pressure).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2. It can be seen that the temperature exerts great influence on caffeine recovery, similar to the ultrasound assisted caffeine extraction from coffee powder during preparation of coffee beverage (Wang et al 2011). Temperature contributes to the extraction efficiency, because it strongly affects the properties of the solvent (decrease of both viscosity and surface tension, and induces an increase in the vapor pressure).…”
Section: Resultsmentioning
confidence: 99%
“…The extraction of caffeine was investigated using ultrasound from other materials, such as from cacao seeds and chocolate (Peralta-Jiménez and Cañizares-Macías 2013), from green tea leaves (Jun 2009;Sereshti et al 2013). Wang et al (2011) applied ultrasound in the preparation of the coffee beverage from roasted and ground coffee, which results indicated strong influence of the extraction temperature (5-95°C) and higher caffeine concentration at 28 kHz than at 40 kHz operating frequencies, under the same extraction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To extract caffeine, the primary alkaloid in coffee, ultrasound is a suitable method. Wang et al [5] found that only a short extraction time was needed to reach the saturation state when using ultrasonic. The results achieved with ultrasonically assisted extraction are also suitable for tea.…”
Section: Introductionmentioning
confidence: 99%